"The President's Prerogative"? The Cabinet Appointment Process in Ghana and the Implications for Gender Parity. Issue 2 (June 2022) - Bauer, Gretchen; Darkwah, Akosua K.
Abstract: This article seeks to understand why Ghana, unlike several other African countries, has seen relatively few women appointed as ministers to the cabinet since the transition to democracy. We draw on Annesley, Beckwith, and Franceschet's 2019 book Cabinets, Ministers and Gender, which provides an in-depth analysis of the cabinet appointment process in seven democracies (but no African cases) and demonstrates that the cabinet appointment process is gendered—that is, men and women have different (and unequal) opportunities to be appointed as cabinet ministers. This article covers Ghana's Fourth Republic, during which women's presence in cabinets has increased slowly but steadily. We rely on media reports from five recent presidential administrations and semistructured, in-depth interviews with selected informants, as well as other primary and secondary sources. We find that while Ghana has a fairly empowered president who could appoint a gender parity cabinet, the formal and informal rules governing the selection of cabinet ministers—for example, those related to regional balance and "minister MPs"—work against more women in the cabinet.